PENGARUH PSYCHOLOGICAL CAPITAL TERHADAP CAREER SUCCESS DENGAN JOB CRAFTING SEBAGAI VARIABEL MEDIASI - Annisa Alfa Setyawan (Jurnal Manajemen dan Pemasaran Jasa, 2019)
The study examined the relationship between psychological capital and career success with job crafting as mediating variable. This research spread the questionnaire surveying a sample of 200 employees from hospitality industry. Result from partial least square that psychological capital was positively associated with both subjective and objective indicators of career success. Job crafting resulted in higher levels of career success. Together, the findings highlight the role psychological capital and job crafting to facilitate career success employees, consistent using both self-report and significant otther ratings of psychological capital.